Mollusc Diversity in Lendang Luar Beach North Lombok - Candri, Dining Aidil; Aulia Zahara, Asha; Engelina Noer Soraya; Aina Ul Mardiati; Slamet Kurniawan Riandinata (Jurnal Moluska Indonesia, 2024)
Mollusks are a group of marine biota that are components of aquatic ecosystems and have an important role in ecological functions. This research was conducted to find out the mollusk species that live in the waters of Lendang Luar Beach, North Lombok Regency. This research was conducted in July 2022 using a purposive sampling method and free sample collection. Based on the inventory results, it was found that there were 20 species of molluscs representing 9 families, of which the most numerous species were from the Strombidae family, namely 5 species. Meanwhile, the fewest species from the Pisaniidae and Cardiidae families are one species each. The highest diversity of Mollusk species is spread across the colon with 11 species of Molluscs, where the dominant habitat of Molluscs is in rocks.